2008
DOI: 10.1099/mic.0.2007/015537-0
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic roles of iron-responsive transcriptional regulator Fur in Burkholderia multivorans

Abstract: The fur (ferric uptake regulator) gene of Burkholderia multivorans ATCC 17616 was identified by transposon mutagenesis analysis. The fur deletion mutant of strain ATCC 17616 (i) constitutively produced siderophores, (ii) was more sensitive to reactive oxygen species (ROS) than the wild-type strain, (iii) showed lower superoxide dismutase and catalase activities than the wild-type strain, (iv) was unable to grow on M9 minimal agar plates containing several substrates that can be used as sole carbon sources by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Bacterial strains and plasmids used in this study are listed in Table 1. Escherichia coli strains were grown at 37°C in Luria-Bertani (LB) broth (48), and Pseudomonas, Sphingomonas, and Burkholderia strains were grown at 30°C in LB broth diluted 1/3 (1/3-LB broth) (74). Solid media were prepared by the addition of 1.5% agar.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial strains and plasmids used in this study are listed in Table 1. Escherichia coli strains were grown at 37°C in Luria-Bertani (LB) broth (48), and Pseudomonas, Sphingomonas, and Burkholderia strains were grown at 30°C in LB broth diluted 1/3 (1/3-LB broth) (74). Solid media were prepared by the addition of 1.5% agar.…”
Section: Methodsmentioning
confidence: 99%
“…The fur product, a ferric uptake regulator, is a global transcriptional regulator for the iron regulon in many Gramnegative bacterial species (Faulkner & Helmann, 2011). As has been noted in other phylogenetically distant bacteria, the Fur protein in ATCC 17616 plays pleiotropic roles in the maintenance of iron homeostasis, removal and/or resistance to reactive oxygen species (ROS) and reactive nitrogen species (RNS), and energy metabolism of carbon and energy sources (Yuhara et al, 2008). We have also indicated that there is a higher level of ferric ion in the ATCC 17616 fur mutant, leading to the generation of a larger amount of very toxic ROS, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of the singly inoculated control strain 2C4-34 did not change after the 20 to 40 day *In the second STM screening (see Table S2). DPositions and locus tag names used are on the basis of our deposited sequences [AP009385, AP009386 and AP009387 for Chr1, Chr2 and Chr3, respectively, in DDBJ/EMBL/GenBank databases Yuhara et al (2008)]. dNo name, no gene name associated with this ORF in the annotated ATCC 17616 genome.…”
Section: Reconstruction Of Disruption Strains Of Five Genesmentioning
confidence: 99%
“…1). The donor was mated with three recipient strains whose genome sequences have been determined: BmGm (a Gm-resistant derivative of B. multivorans ATCC 17616 [31,37]), Sp-UTKm (a Km-resistant derivative of Sphingobium japonicum UT26 [15]), and Pp-KTGm (a Gm-resistant derivative of P. putida KT2440 [16]). ATCC 17616 carries a Tn4371-like element, but UT26 and KT2440 do not.…”
Section: Resultsmentioning
confidence: 99%